2017
DOI: 10.1139/apnm-2017-0119
|View full text |Cite
|
Sign up to set email alerts
|

Antiglycating potential of acesulfame potassium: an artificial sweetener

Abstract: Sweeteners have replaced the natural sugars in the food and beverage industry because of many reasons, such as hyperglycemia and cost. Saccharin, sucralose, aspartame and acesulfame-K are the most commonly used sweeteners. In the present study, the abovementioned artificial sweeteners were used to assess their glycating properties by established methods such as browning, fructosamine assay, determination of carbonyl content, protein aggregation, and measurement of fluorescence. Amadori and advanced glycation e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…This phenomenon could be related to the presence of glucose-like reactive groups that interact with amine groups in lysine. A more recent study has not confirmed these observations and has reported an anti-glycation effect for acesulfame potassium 45,46 .…”
Section: Pathogenic Effectsmentioning
confidence: 90%
“…This phenomenon could be related to the presence of glucose-like reactive groups that interact with amine groups in lysine. A more recent study has not confirmed these observations and has reported an anti-glycation effect for acesulfame potassium 45,46 .…”
Section: Pathogenic Effectsmentioning
confidence: 90%
“…Neurodegenerative disorders (Alzheimer's and Parkinson's disease), diabetes and its vascular complications and early onset of aging have been correlated with the hyperglyce-mic condition and oxidative stress through free radicals' generation and tissue damage (Ali et al 2017;Hammoda 2013;Kim and Kim 2003). The changes in the structure, biological activity, and half-life of proteins cause mutations in nucleic acids, as well as affect transport and signaling processes by causing damage to lipids in the membrane (Tupe et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Artificial sweeteners are not completely metabolized and impart minimal or no calories to the human body (Dhartiben and Aparnathi 2017;DuBois and Prakash 2012). The prevention of formation of fluorescent AGEs by sucralose in fructose-mediated glycation system was described by Deo et al 2020. Ali et al (2017 reported that artificial sweeteners have reversed the formation of glycation products in lysine and glucose system.…”
Section: Introductionmentioning
confidence: 99%
“…Browning was used as a simple colorimetric method for the assessment of the glycation process. The absorbance of the glycated sample in both the presence and the absence of the plant extracts was measured using a Shimadzu UV 1800 spectrophotometer at 420 nm and the relative percentage was calculated using BSA+ Fructose as the standard (100%) (Ali et al 2017). The results are expressed as mean±SEM (n=3).…”
Section: Effects Of the G Cordifolium Extracts On Browningmentioning
confidence: 99%